Analisis Prosedur Gadai Emas Syariah Dan Penerapannya Pada Pegadaian Syariah UPS Mandailing Natal - Ummi Itiah Nasution; Waizul Qarni; Ahmad Kali Ansori Nasution (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
Sharia pawning is called rahn in Islamic law where the meaning is a contract with the detention of valuables as collateral for debts carried out by sharia pawnshops. In my opinion, as a writer, this sharia gold mortgage is the best choice when there are pressing financial matters. This is what makes the author interested in the topic of sharia gold pawning to be studied more deeply. This study discusses the description of the pawnshop itself and the conditions and procedures for pawning gold in sharia at the UPS Mandailing Natal pawnshop. The method used in this study is descriptive qualitative problem approach used is direct interviews and observations. The data used is secondary data including primary, secondary and tertiary data. All data was collected through interviews with managers and service users at UPS Mandailing Natal Sharia Pegadaian as well as literature study. All data is processed by examining data and data settings and then analyzed. The procedure uses a rahn contract and an ijarah contract. Factors that make Islamic Gold Pawning a solution for the lower middle class in Mandailing Natal Regency are because there is no usury or interest and it is more cost-effective as well as collateral items are safer.